2013
DOI: 10.1016/j.bone.2013.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal progression of bone disease in the cervical spines of mucopolysaccharidosis I dogs

Abstract: Introduction Mucopolysaccharidosis I (MPS I) is a lysosomal storage disorder characterized by deficient α-L-iduronidase activity leading to accumulation of poorly degraded dermatan and heparan sulfate glycosaminoglycans (GAGs). MPS I is associated with significant cervical spine disease, including vertebral dysplasia, odontoid hypoplasia, and accelerated disc degeneration, leading to spinal cord compression and kypho-scoliosis. The objective of this study was to establish the nature and rate of progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Studies using the naturally-occurring canine models of MPS I and MPS VII have described similar failures of ossification in the peripheral regions the vertebral bodies [8, 106]. At 6 weeks-of-age, there is clear evidence of delayed and dysregulated bone formation in the secondary ossification centers of the vertebrae, as well as elevated GAG content within the annulus fibrosus that persist into older ages in MPS VII dogs (Figure 2).…”
Section: Pathophysiology Of Spine Disease In Mpsmentioning
confidence: 86%
See 3 more Smart Citations
“…Studies using the naturally-occurring canine models of MPS I and MPS VII have described similar failures of ossification in the peripheral regions the vertebral bodies [8, 106]. At 6 weeks-of-age, there is clear evidence of delayed and dysregulated bone formation in the secondary ossification centers of the vertebrae, as well as elevated GAG content within the annulus fibrosus that persist into older ages in MPS VII dogs (Figure 2).…”
Section: Pathophysiology Of Spine Disease In Mpsmentioning
confidence: 86%
“…At 6 weeks-of-age, there is clear evidence of delayed and dysregulated bone formation in the secondary ossification centers of the vertebrae, as well as elevated GAG content within the annulus fibrosus that persist into older ages in MPS VII dogs (Figure 2). In the vertebral secondary ossification centers of 6 month-old MPS VII dogs, elevated levels of GAGs and reduced calcium indicated the presence of cartilage rather than bone [106]. Biomechanical evaluations showed that vertebral endplates adjacent to these cartilaginous lesions are mechanically extremely weak, leading to reduced stiffness and hypermobility of the intervertebral joints, implicating these lesions in the progression of deformity [105].…”
Section: Pathophysiology Of Spine Disease In Mpsmentioning
confidence: 99%
See 2 more Smart Citations
“…MPS I is associated with vertebral abnormalities, similar to those observed in the dog of this report. These include generalised abnormalities most prominent in the cervical region and are characterised by trabecular bone loss, delayed cartilage to bone conversion, vertebral dysplasia, collapsed intervertebral disc spaces, intervertebral disc herniation and increased fracture risk (Chiaro and others 2013). The dog presented in this report also suffered from long-standing elbow disease.…”
Section: Discussionmentioning
confidence: 99%